Brucellosis in mammals of Costa Rica: An epidemiological survey - Hernández Mora, Gabriela (2017)
Brucellosis has been an endemic disease of cattle and humans in Costa Rica since the beginning of XX century. However, brucellosis in sheep, goats, pigs, water buffaloes, horses and cetaceans, has not been reported in the country. We have performed a brucellosis survey in these host mammal species, from 1999–2016. In addition, we have documented the number of human brucellosis reported cases, from 2003–2016. The brucellosis seroprevalence in goat and sheep herds was 0.98% and 0.7% respectively, with no Brucella isolation. Antibodies against Brucella were not detected in feral or domestic pigs. Likewise, brucellosis seroprevalence in horse and water buffalo farms was estimated in 6.5% and 21.7%, respectively, with no Brucella isolation. Six cetacean species showed positive reactions against Brucella antigens, and B. ceti was isolated in 70% (n = 29) of striped dolphins (Stenella coeruleoalba). A steady increase in the diagnosis of human brucellosis cases was observed. Taking into account the prevalence of brucellosis in the various host mammals of Costa Rica, different measures are recommended.